Faktor penentu loyalitas penumpang kereta api antarkota lintas Pulau Jawa - Effendi, Hernita; Yenita, Yenita (Universitas Kristen Maranatha, 2023)
PT Kereta Api Indonesia (KAI) is a monopolist company that has no competitors in the field of rail transportation services, but in Java Island is vulnerable to competitors in the field of other land transportation services. In 2022, the number of intercity train passengers throughout Java non-Jabodetabek seems to be fluctuating, this is possible because people are not satisfied with train services. This research is intended to unravel the influence of customer experience, trust, and satisfaction that can affect customer loyalty. Partial Least Square (PLS) was used to process the data in this study. The sample in this study was a customer of the cross-Java intercity railway with purposive sampling technique. The results showed that customer experience affects satisfaction. Customer trust also affects satisfaction. Then customer experience is proven to affect customer loyalty, but customer trust is not proven to affect customer loyalty. Furthermore, trust is proven to affect customer loyalty. Customer experience mediated by satisfaction is also proven to affect customer loyalty. Customer trust is also proven to be able to influence customer loyalty through satisfaction. The analysis proves that experience and trust affect the customer satisfaction of cross-Java intercity train customers, then experience and satisfaction affect the customer loyalty of cross-Java intercity train customers, but not with trust, and also customer loyalty of cross-Java intercity train customers is influenced by experience and trust through customer satisfaction mediation. For PT KAI, this research has implications for the vitality of passenger loyalty by creating a good experience and passenger trust.